Association schemes : designed experiments, algebra, and combinatorics - Bailey, R. (Rosemary) (Cambridge studies in advanced mathematics ;, 2004)
Based on the author's graduate course on association schemes and the optimal design of scientific experiments, this book is accessible to both pure mathematicians and statisticians alike. It will appeal to researchers as an accessible reference work from which to learn about the statistical/combinatorial aspect of their work.